2017
DOI: 10.1158/1078-0432.ccr-17-1535
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures and Immunohistochemical Subtypes Add Prognostic Value to Each Other in Breast Cancer Cohorts

Abstract: Purpose Gene signatures and Ki67 stratify the same breast tumor into opposing good/poor prognosis groups in approximately 20% of patients. Given this discrepancy, we hypothesized that the combination of a clinically relevant signature and IHC markers may provide more prognostic information than either classifier alone. Experimental Design We assessed Ki67 alone or combined with ER, PR and HER2 (forming IHC subtypes), and the research versions of the Genomic Grade Index, 70-gene, cell-cycle score, recurrence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 37 publications
4
49
0
Order By: Relevance
“…Although tumor grade is also a marker of proliferation, gene expression signatures have been reported to add prognostic information beyond that provided by tumor grade . In addition, a recent study reported that gene expression signatures failed to provide significant prognostic information beyond Ki‐67 in ER + /LN – patients, whereas all signatures demonstrated prognostic strength beyond Ki‐67 or immunohistochemical subtypes in ER + /LN + patients . This may imply that contralateral BPE may provide less additional information after consideration of tumor proliferation activity, and further risk stratification beyond Ki‐67 would be even more difficult in ER‐positive, LN‐negative patients, who already have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although tumor grade is also a marker of proliferation, gene expression signatures have been reported to add prognostic information beyond that provided by tumor grade . In addition, a recent study reported that gene expression signatures failed to provide significant prognostic information beyond Ki‐67 in ER + /LN – patients, whereas all signatures demonstrated prognostic strength beyond Ki‐67 or immunohistochemical subtypes in ER + /LN + patients . This may imply that contralateral BPE may provide less additional information after consideration of tumor proliferation activity, and further risk stratification beyond Ki‐67 would be even more difficult in ER‐positive, LN‐negative patients, who already have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that our cell cycle score gene expression signature, previously established in a breast cancer setting [11,12], provided independent prognostic information on a pan-cancer level. This signature was originally conceived as simple biological measure of cell cycle activity in response to the dependence of more established commercial gene expression signatures on multiple cell cycle/cell proliferation genes for their prognostic capacity [19].…”
Section: Discussionmentioning
confidence: 76%
“…Clusters with less than 20 tumours were excluded from further analysis. Cell Cycle Score (CCS) signature was applied as previously published [11,12]. Briefly, we extracted gene expression data from 433 of 463 signature CCS genes from all pan-cancer tumours and summed their values on an individual tumour basis to derive a single score of cell cycle activity for each sample.…”
Section: Mrna Data Clustering and The Cell Cycle Score (Ccs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Signatures were chosen on the basis of their relevancy in an on-going Swedish clinical trial (20) and owing to their use in a routine clinical setting. The cell-cycle score (CCS) was derived by adding the expression of cell-cycle genes identified from three different databases (KEGG, HGNC, Cyclebase) and splitting the resulting continuous variable into tertiles of low, intermediate, and high cell-cycle activity, further details here (21). …”
Section: Methodsmentioning
confidence: 99%